Building a nursing legacy. Issue 8 (August 2021) - Graber, Jennifer; Saylor, Jennifer; Jackson, Amy; Hayes, Evelyn
Abstract : Abstract: A nurse's legacy can be defined in multiple ways. This article describes a project based on a qualitative research study that focused on legacy building in nursing. Abstract : To comprehend what it means to be a nurse, one must understand the career spectrum from nursing students to veteran experts in the field. This article describes a project based on a qualitative research study that focused on legacy building in nursing.